Circular Economy and its Indicators for Russia - S. N. Bobylev; S. V. Solovyeva (Мир новой экономики, 2020)
In the world, the theory of the circular economy and its formation in the real economic system is rapidly developing. Many international organizations (OECD, EU) and countries already have their programs for developing such an economy. The article emphasizes that the practical implementation of the concept of “best available technologies” is vital for the transformation of the current linear model of the economy in many countries, including Russia. In Russia, there are many obstacles to the formation of a circular economy; the inertia of the existing export-raw material model is excellent, which is unsustainable and linear. A dangerous trend is the growth of waste intensity at the macro level. The article analyzes and adapts for Russia the UN Sustainable Development Goals directly related to the circular economy, proposes and quantifies key indicators. In the field of quantitative indicators, four areas have been identified for the development of crucial indicators set for the circular economy in Russia. An author’s formula for structuring the consumption of natural resources taking into account technological efficiency and waste is proposed. The importance of using the proposed toolkit of natural-product verticals combining primary natural resources / raw materials with final consumption and allowing us to estimate the size of the lost primary natural resources is emphasized. The indicators of waste management, in combination with production and consumption systems, are analyzed. For a circular economy, it is fundamentally important to calculate the resource and material intensity indicators of various sectors and their weight in the gross product, which will allow to assess the impact of potential structural changes on waste generation and conduct a comparative analysis with the corresponding indicators of other countries.